Unusual psoas metastasis of a primary colic adenocarcinoma: A case report - Mohammed Bendimya, MD; Soufia El Ouardani, MD; Ouissam Al Jarroudi, MD; Sami Aziz Brahmi, MD; Said Afqir, MD (Radiology Case Reports)
Colorectal cancer ranks as the third most prevalent cancer globally; however, skeletal muscle metastases that originate from colonic adenocarcinoma are exceedingly rare. This article describes the treatment of a 63-year-old woman diagnosed with colonic cancer classified as T3N1M0. Three months later, the patient presented with multiple pulmonary and peritoneal metastases, with a psoas muscle metastasis confirmed through pathological examination. The characteristics and challenges of muscle metastases originating from primary adenocarcinoma will be discussed.